A Quantitative Approach to Selecting SUDS for Flood Resilience in Can Tho City, Mekong Delta - Huynh, Trong Nhan; Nguyen, Hong Tien; Le, Ho Tuyet Ngan (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study develops a quantitative framework for selecting Sustainable Urban Drainage Systems (SUDS) to enhance flood resilience in an area formerly under Soc Trang City, now administratively designated as Phu Loi Ward, Soc Trang urban area of Can Tho City, Mekong Delta, a region vulnerable to urban inundation due to low elevations (1.5–1.6 m) and inadequate drainage infrastructure. This is the first framework of its kind applied in Can Tho or in secondary Mekong Delta cities, offering a novel, context-specific approach to flood-risk management. The framework integrates geospatial analysis using QGIS, runoff estimation via the SCS-CN method, and a multi-criteria SUDS Selection Score (SSS) evaluating flood mitigation performance, cost-effectiveness, feasibility, and co-benefits as urban cooling, cultural value. Applied to the Phan Boi Chau Street pilot, the framework assessed SUDS measures, including bio-swales, permeable pavements, and storage tanks. Results demonstrate significant runoff reduction and improved urban aesthetics, validated through stakeholder engagement with Khmer communities through site surveys. The framework’s replicability offers a scalable model for flood-prone cities in the Mekong Delta and beyond, supporting evidence-based, community-sensitive flood management planning.